Drafting Italy : conscription and the military from 1814 to 1914 - Rovinello, Marco (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This is the first comprehensive history of conscription and the military in Italy from the Restoration to the eve of WWI. The comparative and transnational approach enables this work to compare and contrast the Italian experience with that of many other countries in the world as well as understand transfers and the adaptive and imitative processes that emerge when conscription and the military are viewed from an Italian perspective. Peacetime and wartime recruitment, military life, culture, justice and civil-military relationships are analysed using a wide range of sources and an interdisciplinary approach that combines top-down and bottom-up perspectives. This enables the book not only to assess the contribution the military has made to the country in terms of state-building, nation building, modernization, pedagogical and disciplinary models, gender identity and roles, but also to reconsider the standard taxonomies as well as some established evolutionary models of the armies. Moreover, the Italian military is seen as an internally complex world that is incapable of defining its own one-dimensional identity or of imposing any such identity on its members. Consequently, it is an element in the history of a country that is substantially the same as any other such element and thus important in people's collective and individual lives whether or not they are in uniform. Rather than being an object of study in and of itself, the military becomes a vantage point from which to observe the Italian history in the long 19th century. Therefore, this book can be profitably read by professional military historians and non-specialist readers interested in the military, as well as by all scholars working on Italian pre- and post-unification political, institutional, socio-economic, cultural and gender history"--
The military as a window on Italian history -- Why conscription? -- Why the long 19th century? -- The structure of the book -- Redrafting the draft (1814-1859) -- Change and continuity in post-Napoleonic recruitment -- The armies of pre-unification Italian states -- The army of the Two Sicilies -- The army of the Kingdom of Sardinia -- Drafting a nation, building a State (1859-1866) -- Building up a national army in wartime -- From exception to norm -- Professional conscripts -- Civilising rough recruits -- Us and Them -- Civil war and 'shameful defeats' -- Depicting the military -- A qualified revolution (1866-1876) -- The post-1866 debate -- Italianising the German model -- The demise of the semi-professional army -- A true 'school of the nation'? -- One-year volunteers -- Drafting souls -- A greater army for an aspiring Great Power (1876-1900) -- Gradual incremental reform -- Gearing up for expansion -- Pushing forward in the 1890s -- Militarising society -- Anti-socialist machismo -- Discipline, punish and turn a blind eye -- A desperate malaise -- In the field -- From peace to war (1901-1914) -- Going global -- Serve less, serve all -- Tension and disquiet -- The propaganda war -- The catechism of war -- Trouble and strife -- Destination Libya -- Turning the page (1915-1918) -- The world mobilises -- The last great army, the first minor army -- Old war machine, new warfare -- The pre-1915 legacy.
Keywords: Draft -- Italy -- History -- 19th century; Draft -- Italy -- History -- 20th century; HISTORY / General; HISTORY / Europe / Italy; HISTORY / Military / World War I